Trends in Monkeypox transmission: Investigation into 30 most affected countries - Salman A. Cheema; Tahir Munir; Kalim Ullah; Tanveer Kifayat; Abdur Rahman; Walid Emam; Yusra Tashkandy; Saima K. Khosa; Ahmad Zubair (Heliyon, 2024)
This research is based on the analysis of Monkeypox transmission, from may 7, 2022 to October 11, 2022, in 30 most affected countries around the globe. The most affected countries are selected through the cut point of at least 100 reported confirmed cases of infected persons over the aforementioned time span. We novely argue the exhibition of distributional similarities between the viral flow and well known power law in context of this neglected zoonotic disease. Moreover, model-based evidence suggesting the capability of pathogen to spread far and wide around its nucleus, are collected and presented. It is estimated that 70 % of the reported confirmed cases belonged to 20 % of the top most affected countries. Also, 70 % of the reported transmission was inflicted in 34 % of the days of reporting at least one case, on average.